Amazonian Amphibian Diversity Is Primarily Derived from Late Miocene Andean Lineages - Santos, Juan C.; Coloma, Luis A.; Summers, Kyle; Caldwell, Janalee P.; Ree, Richard; Cannatella, David C. (East Carolina University, 2009)
The Neotropics contains half of remaining rainforests and Earth’s largest reservoir of amphibian biodiversity. However, determinants of Neotropical biodiversity (i.e., vicariance, dispersals, extinctions, and radiations) earlier than the Quaternary are largely unstudied. Using a novel method of ancestral area reconstruction and relaxed Bayesian clock analyses, we reconstructed the biogeography of the poison frog clade (Dendrobatidae). We rejected an Amazonian center-of-origin in favor of a complex connectivity model expanding over the Neotropics. We inferred 14 dispersals into and 18 out of Amazonia to adjacent regions; the Andes were the major source of dispersals into Amazonia. We found three episodes of lineage dispersal with two interleaved periods of vicariant events between South and Central America. During the late Miocene, Amazonian, and Central American-Chocoan lineages significantly increased their diversity compared to the Andean and Guianan-Venezuelan-Brazilian Shield counterparts. Significant percentage of dendrobatid diversity in Amazonia and Choco´ resulted from repeated immigrations, with radiations at ,10.0 million years ago (MYA), rather than in situ diversification. In contrast, the Andes, Venezuelan Highlands, and Guiana Shield have undergone extended in situ diversification at near constant rate since the Oligocene. The effects of Miocene paleogeographic events on Neotropical diversification dynamics provided the framework under which Quaternary patterns of endemism evolved. Originally published PLoS Biology, Vol. 7, No. 3, Mar 2009
Keywords: Neotropic; Amphibian biodiversity; Miocene